Effects of Location on Performance of Selected Tropical Maize Hybrids Developed in Malaysia - Saleh, Ghizan; Daud, Abdullah; Abd Rahim, Anuar (Universiti Putra Malaysia Press, 2002)
Eighteen selected locally-developed maize hybrids involving ten single, four double and four three-way crosses were evaluated with two open-pollinated check varieties (Metro and Suwan 1) at three locations in Peninsular Malaysia. The study was aimed to compare performance among the hybrids at the locations separately and when combined, to evaluate the genotype x location interaction revealed for yield and other important traits, and to estimate the heritability of the traits. Many hybrids were found to have out-yielded the check varieties. Significant effects of location for grain yield and most other traits indicated that the environmental and growth factors characterising the locations considerably affected the performance of the hybrids. Genotype x location interactions were not significant for the important traits, indicating that the ranking in performance of the genotypes was consistent among locations. Performance of the hybrids was best in Terengganu as compared to Selangor and Perlis. Higher heritability estimates for characters when measured in Terengganu further revealed the uniformity of environmental factors governing maize growth in that location. Based on the overall performance, three single crosses (SC-1, SC-2 and SC-8), one double cross (DC-11) and two three-way crosses (TWC-15 and TWC-17) were found to be highly potential for further trials towards new variety release.